2015
DOI: 10.3390/membranes5040553
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Target of Rapamycin and Other Phosphatidylinositol 3-Kinase-Related Kinases by Membrane Targeting

Abstract: Phosphatidylinositol 3-kinase-related kinases (PIKKs) play vital roles in the regulation of cell growth, proliferation, survival, and consequently metabolism, as well as in the cellular response to stresses such as ionizing radiation or redox changes. In humans six family members are known to date, namely mammalian/mechanistic target of rapamycin (mTOR), ataxia-telangiectasia mutated (ATM), ataxia- and Rad3-related (ATR), DNA-dependent protein kinase catalytic subunit (DNA-PKcs), suppressor of morphogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 150 publications
(277 reference statements)
1
11
0
1
Order By: Relevance
“…The mammalian PIKK family constitutes of six proteins, namely: mammalian target of rapamycin (mTOR), ataxia-telangiectasia mutated (ATM), ATR, DNA-dependent protein kinase (DNA-PK), suppressor of morphogenesis in genitalia-1 (SMG-1), and transformation/transcription domain-associated protein (TRRAP). Unlike canonical PI3 kinases, the PIKKs lack lipid phosphorylation activity and function as protein kinases instead [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian PIKK family constitutes of six proteins, namely: mammalian target of rapamycin (mTOR), ataxia-telangiectasia mutated (ATM), ATR, DNA-dependent protein kinase (DNA-PK), suppressor of morphogenesis in genitalia-1 (SMG-1), and transformation/transcription domain-associated protein (TRRAP). Unlike canonical PI3 kinases, the PIKKs lack lipid phosphorylation activity and function as protein kinases instead [10] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that targeted membrane localization allows spatial separation of individual signaling branches of large signaling networks, thereby potentially improving the reliability of biochemical signaling processes (19). Because PIKKs generally participate in a multitude of signaling pathways in response to ionizing radiation and other stress factors or metabolic signals (2,5,7,16,20,21), their localization may also determine the specific signaling output (22). ATM has been found to localize and function not only in the nucleus but also in the cytoplasm (12).…”
mentioning
confidence: 99%
“…TOR has been detected at different cellular membranes and in the nucleus. Based on these observations it has been suggested that the localization of TOR depends on the composition of the TOR complexes as well as on the cell type and signaling state and is mediated by an extensive network of protein‐protein and protein‐lipid interactions . The solution structure of the oxidized FATC domain of yeast TOR1 [residues 2438–2479, y1fatc, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the significantly lower sample concentration of SUVs compared to micelles and bicelles as well as their larger radius and thus lower membrane curvature. The FATC domain is shared by all members of the family of phosphatidylinositol‐3 kinase‐related kinases (PIKKs), which control cellular signaling pathways in response to stress and nutrients . All have been shown to interact with membrane mimetics albeit with differences in the preferences for specific membrane properties …”
Section: Introductionmentioning
confidence: 99%